Factors Relating to Restraint Implementation for Patients with Violence Behavior in Madani Hospital - Iwan Iwan; Azizah Saleh (Alliance oh Health Activists (AloHA), 2019)
Nurses have not fully provided care in accordance with the standards that exist in patients undergoing fixation. This could have happened because there is still a lack of nurses' knowledge about the fixation action. This study aimed to determine the factors relating to the implementation of restraint in patients with violence behavior in the Madani Hospital in Central Sulawesi Province. This research was an analytic study with the cross sectional design. The population in this study were all nurses in the nurses' room in Madani District Hospital, Central Sulawesi Province. Population size = 76 people, and sample size = 43 people. Data were collected using a questionnaire and analyzed using Chi-square test. There was a significant relationship between knowledge and attitude of nurses with the implementation of restrain in the mental care room of Madani Hospital with p-value of 0.003 and 0.000. There was no correlation between the experience with the implementation of restrain in the mental care room of Madani Hospital with p-value of 1.000. Keywords: knowledge, attitude, experience, restraint, nurse